2021
DOI: 10.1021/acsnano.1c04864
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Visualization of Lithium Penetration through Solid Electrolyte and Dead Lithium Dynamics in Solid-State Lithium Metal Batteries

Abstract: The two biggest promises of solid-state lithium (Li) metal batteries (SSLMBs) are the suppression of Li dendrites by solid-state electrolyte (SSE) and the realization of a high-energy-density Li anode. However, LMBs have not met their expectations due to Li dendrite growth causing short-circuiting. In fact, Li dendrites grow even more easily in SSE than in liquid electrolyte, but the reason for this remains unclear. Here we report in situ transmission electron microscopy observations of Li dendrite penetration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 61 publications
0
44
0
Order By: Relevance
“…It has been used to study the lithium dendrite growth process. [38][39][40] For example, lithium penetration through an Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 (LLZTO) SSE was revealed, 38 and a direct measurement of the growth force was conducted. 39,40 However, the quantitative details on the electrochemomechanics during the penetration process is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used to study the lithium dendrite growth process. [38][39][40] For example, lithium penetration through an Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 (LLZTO) SSE was revealed, 38 and a direct measurement of the growth force was conducted. 39,40 However, the quantitative details on the electrochemomechanics during the penetration process is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…These results are similar to those shown in a recent report by Sun et al , where the authors revealed that during Li deposition on the Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 (LLZTO) solid-state electrolyte, some dark particles broke off from the LLZTO bulk and were carried away by Li dendrite. 53…”
Section: Resultsmentioning
confidence: 99%
“…To depict more surface details of these dendrites, (LLZTO) solid-state electrolyte, some dark particles broke off from the LLZTO bulk and were carried away by Li dendrite. 53 To further understand the accumulation of zinc at the bottom of the Li nuclei, elemental mapping images were collected at high magnication on the top surface of the sample (Fig. 2d).…”
Section: Nucleation Mechanismmentioning
confidence: 99%
“…[28] Once commenced, the deposited Li accumulates and propagates along the flaws of the SSE as well as the grain boundaries, causing SSE fracture or a cell short circuit. [29] The process of Li accumulation in preexisting voids of the SSEs is identified into three stages: metal plating initiation, metal growth, and metal compression.…”
Section: Consideration Of the Failure Modes Of Ssesmentioning
confidence: 99%